International collaborations in learning and teaching: perspectives from a visiting professorship. (9th August 2016) - Spring, Hannah; Kunkel, Marita; Gilman, Isaac; Henderson, Nancy; White, John
Abstract: This article provides a reflection on the outcomes of an international collaboration between health librarians and academics at York St John University and Pacific University Oregon. In particular, it describes how a month‐long visiting professorship from an academic with a clinical librarian background at the Faculty of Health and Life Sciences helped to develop and inform teaching practice in the areas of information literacy and evidence‐based health practice on health programmes at Pacific University. Perspectives are offered from both institutions on the rich exchange of knowledge and practice that took place during the visit and the ongoing impact it has had on teaching practices. H. S.